Prognostic value of GCS, APACHE ii and CT scan of the head in predicting early mortality in severe head injury. - Pradhan, Sidhartha (2001)
ABSTRACT: A prospective study to evaluate the validity of APACHE II score, Glasgow Coma Scale and the plain CT scan of the head in predicting short-term outcome in patients with severe head injury, was undertaken at the Neuro Surgery unit of the Department of surgery at T.U. Teaching Hospital between Asadh 2057 and Baishakha 2058. The total number of patients admitted to the ICU with Glasgow Coma Scale of less than nine, were 32. There were 27 male and 5 female patients. There were nine mortalitites within the first week of admission, amongst the 32 patients. The most common modes of injury were a fall from a height (13,40.6%) and road traffic accident (13,40.6%). 23 (71.9%) of the 32 severely head injured patients either had sustained unconsciousness or had lost consciousness for more than 30 minutes. 13 (40.6%) of the 32 patients had abnormal papillary reaction. 16 (50%) of the patients had type II injury, as per Marshall's classification for Diffuse Brain Injury and was the most common. The average age of the severely head injured was 29.3 +-12.2 years, the average duration since the time of injury was 11.34 +- 13.39 hours. The average MAP was 83.3 +- 18.7 mmHg. The average heart rate was 91.9 +- 19.56 beats per minute. The average FiO2 of 57 +- 0.24%, the average alveolar ¬_ arterial oxygen difference was 240.7 +- 131.9, the PaO2 was 130.4 +-67.6 mmHg, the PaCO2 was 36.3 +- 7.45 mmHg. The average APACHE II score was 13.87 +- 4.37, and the average Glasgow Coma Scale was 6.37 +- 1.56. There was no significant difference between the surviving and the mortality groups with regard to APACHE II (13.9 vs. 14.3, p = 0.85) & GCS (6.54 vs. 5.90, p=0.47). The factors that were found to determine mortality in the severely head injured patients were duration since the injury (p = 0.0003), the mean arterial pressure at presentation (p=0.02), the heart rate (P= 0.03) the fraction of inspired oxygen (p=0.003), the alveolar _ arterial oxygen difference (p = 0.01), the arterial pH (P=0.005), with p-value <0.05, considered to be significant. The CT Scan finding of grade four injury, was also associated with a high early mortality. Thus, the severely head injured patients are a non-homogenous group of patients with variable degree of circulatory and respiratory compromise due to the insult to the brain and external/internal bleed. Such a compromise may not be immediately evident by the change in hermatocrit, the renal function or the electrolytes, but can be detected by the change in the circulatory and respiratory parameters. The plain CT Scan of the head can delineate the severity of the brain injury and thus help in the prognostication of such an injury, as well as determine the necessity for surgical intervention. To conclude, in our set up, the APACHE II score, seems to be inadequate in predicting early mortality, and that the collection of the complete data of the APACHE II score is cumbersome, time consuming and expensive. On the other hand, the Glasgow Coma seemed to homogenize the patient population into the "severe" category, thus limiting its usefulness when considered as a whole. But selective monitoring of the respiratory and circulatory parameters; along with CT Scan imaging may help in the prognosis of severely head injured patients.